A simple paper-strip colorimetric method utilizing dehydrogenase enzymes for analysis of food components1. Issue 19 (7th October 2015) - Monošík, Rastislav; Bezerra dos Santos, Vagner; Angnes, Lúcio
<x xml:space="preserve">Abstract</x> A simple chromatographic paper based colorimetric assay for the analysis of selected food compounds.